2016
DOI: 10.1007/s10482-016-0757-7
|View full text |Cite
|
Sign up to set email alerts
|

Ophiostomatoid fungi associated with mangroves in South Africa, including Ophiostoma palustre sp. nov.

Abstract: Mangrove trees are continuously under stress due to environmental and/or anthropogenic pressures, which expose them to attack by pathogens, compromising their survival.Ophiostomatoid fungi cause sap stain and diseases of a wide spectrum of tree species globally. These fungi infect trees through natural, insect, animal and/or human made wounds.During routine surveys of mangrove trees in South Africa, wounds on branches and stems of Avicennia marina were regularly monitored for the presence of ophiostomatoid fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
3
6
0
Order By: Relevance
“…Ophiostoma and Sporothrix species were detected as the dominant wound‐associated members of the Ophiostomatales in this study, confirming the results of previous surveys (Kamgan Nkuekam et al , , , , ; Musvuugwa et al , ; Osorio et al , ). The results also highlighted that Leptographium species are common fungi infesting wounds on hardwood trees.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Ophiostoma and Sporothrix species were detected as the dominant wound‐associated members of the Ophiostomatales in this study, confirming the results of previous surveys (Kamgan Nkuekam et al , , , , ; Musvuugwa et al , ; Osorio et al , ). The results also highlighted that Leptographium species are common fungi infesting wounds on hardwood trees.…”
Section: Discussionsupporting
confidence: 91%
“…This result demonstrates that wounds on hardwood trees in Europe are suitable habitats for the Ophiostomatales. This finding was previously documented from some angiosperms in South Africa (Kamgan Nkuekam et al , , ; Musvuugwa et al , ; Osorio et al , ), Australia (Kamgan Nkuekam et al , ) and South America (Geldenhuis et al , ; De Errasti et al , ). In contrast, one European study showed a relatively low diversity of Ophiostoma spp.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This species, which is morphologically indistinguishable from O. quercus , is known from wounds on planted Eucalyptus and Acacia mearnsii trees in Africa ( Grobbelaar et al 2010 ), Australia ( Kamgan Nkuekam et al 2011 ) and China ( Grobbelaar et al 2011 ), as well as native mangroves in South Africa ( Osorio et al 2016 ). The only insects from which the fungus has previously been reported are nitidulid beetles ( Kamgan Nkuekam et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%